Patch Testing With Formaldehyde 2.0% (0.60 mg/cm2) Detects More Contact Allergy to Formaldehyde Than 1.0%. Issue 6 (November 2019) - Isaksson, Marléne; Ale, Iris; Andersen, Klaus E.; Goh, Chee-Leok; Goossens, An; Jerajani, Hemangi; Matsunaga, Kayoko; McFadden, John; Bruze, Magnus
Abstract : Background: The International Contact Dermatitis Research Group increased the patch test concentration of formaldehyde from 1.0% aqueous (aq) to 2.0% aq (in 2011). Objective: This study was designed to investigate the outcome of the decision. Methods: Consecutive dermatitis patients in 8 different clinics were patch tested with formaldehyde 1.0% aq and 2.0% aq. The test solutions were applied with a micropipette to the filter paper discs in the respective chamber. Results: A total of 2778 patients were tested with 1.0% aq and 2766 to 2.0% aq. Sixty-five patients (2.3%, calculated from 2766 tested, to 2.0% aq) had positive patch test reactions interpreted as contact allergy to formaldehyde. This is a rather low frequency. Of these 65, 46 were women (46/1703 [2.7%]) and 19 were men (19/1063 [1.8%]). Thirty-six reacted only to 2.0% aq, 21 patients reacted to both concentrations, and 8 patients reacted only to 1.0% aq. Significantly, more patients reacted to 2.0% aq compared with 1.0% aq ( P < 0.001). There was no significant sex difference. A total of 0.8% irritant reactions were recorded to formaldehyde 2.0% aq and 0.1% to 1.0% aq. Conclusions: The increased formaldehyde patch test concentration to 2.0% aq revealed more formaldehyde contact allergy.